Impact of a Surgical Site and an Anesthetic Method on Hemostatic Disorders - P. A. Lyuboshevsky; A. V. Zabusov; N. I. Artamonova (Общая реаниматология)
Objective: to study hemostatic changes during abdominal operations in relation to the mode of anesthesia, as well as the lower incidence of perioperative hemostatic complications. Subjects and methods. Two hundred patients were examined during elective high-traumatic abdominal operations in relation to the surgical site (the upper or lower abdomen) and anesthetic method (total intravenous anesthesia alone or in combination with epidural (prolonged) or spinal anesthesia). The intensity of postoperative pain syndrome, the time course of changes in plasma cortisol concentrations, the readings of a coagulogram and an agreggatogram, the rate of venous thromboses, thromboembolisms, bleedings, and blood transfusions were examined. Results. Prolonged epidural anesthesia was followed by a considerable reduction in the manifestations of the postoperative pain syndrome and by a limited increase in plasma cortisol concentrations. Without significantly affecting the quality of postoperative analgesia, spinal anesthesia also, nevertheless, inhibited a cortisol response effectively. Postoperative hemostatic parameters characterized the hypercoagulation with a higher platelet aggregation, which was followed by accelerated fibri-nolysis when isolated general anesthesia was applied. The use of both regional anesthetic modes limited the activation of the hemostatic system and prevented accelerated fibrinolysis. The rate of thromboembolic events was low (4%) and did not significantly differ between the groups while there was a less need for blood transfusions when regional anesthesia was employed. Conclusion. By ensuring a more adequate antinociceptive protection, regional anesthesia promotes less perioperative hemo-static changes, which reduces a need for blood transfusions and creates prerequisites for lowering the rate of thromboembol-ic and hemorrhagic events. Key words: abdominal surgery, regional anesthesia, hemostasis, thromboembolic events, bleeding, blood transfusion.